2006
DOI: 10.1016/j.jfoodeng.2005.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing conditions for enzymatic clarification of banana juice using response surface methodology (RSM)

Abstract: Raw banana juice is turbid, viscous and gray in colour. This work was initiated to optimize the enzymatic clarification process of banana juice using response surface methodology. Banana juice was treated with pectinase at various enzyme concentrations (0.01-0.1%), temperatures (30-50°C) and time (30-120 min) of treatment. The effect of these enzyme treatments on filterability, clarity, turbidity and viscosity of the juice were studied by employing a second order central composite design. The coefficient of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
182
0
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(211 citation statements)
references
References 25 publications
16
182
0
13
Order By: Relevance
“…The interaction effect between enzyme concentration and incubation temperature was significant (p< 0.01) and its effect was negative on viscosity as evident from Table 2, meaning that the action of enzyme was dependent on the incubation temperature during enzyme treatment. Lee et al (2006) reported that the rate of enzymatic action increase with increase in temperature. Abdullah et al (2007) and Sin et al (2006) also reported that enzymatic action upon the pectin, leading to a reduction of WHC, releasing free water into the system and reducing the viscosity of the juice Turbidity In preparation of fruit juices, haziness is the major problem due to the presence of pectins.…”
Section: Juice Recovery Perusal Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…The interaction effect between enzyme concentration and incubation temperature was significant (p< 0.01) and its effect was negative on viscosity as evident from Table 2, meaning that the action of enzyme was dependent on the incubation temperature during enzyme treatment. Lee et al (2006) reported that the rate of enzymatic action increase with increase in temperature. Abdullah et al (2007) and Sin et al (2006) also reported that enzymatic action upon the pectin, leading to a reduction of WHC, releasing free water into the system and reducing the viscosity of the juice Turbidity In preparation of fruit juices, haziness is the major problem due to the presence of pectins.…”
Section: Juice Recovery Perusal Ofmentioning
confidence: 99%
“…Increase in yield and clarity and decreases in viscosity in fruit juices have been reported by use of pectin degrading enzymes in dates , peach (Santin et al 2008), banana (Lee et al 2006), mosambi (Rai et al 2004), kiwi fruit (Dawes et al 1994) and pineapple (Sreenath et al 1994). The enzymatic hydrolysis of pectic substances depends on incubation time, temperature and enzyme concentration (Abdullah et al 2007;Lee et al 2006;Sin et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RSM is an effective tool for optimizing complex processes and has been widely applied in the food industry (Wong et al 2003;Lee et al 2006;Sin et al 2006). A CCRD was constructed using software package Statistica (1999).…”
Section: Experimental Designmentioning
confidence: 99%
“…Response surface methodology is one of the most efficient tools for optimizing bio-systems because it makes it possible to evaluate the interactive effects among the variables being studied (RAI et al, 2004;LEE et al, 2006). The optimization of operating parameters for enzyme treatments involving the application of pectinase have already been studied in the case of banana juice (LEE et al, 2006), star fruit juice (ABDULLAH et al, 2007), sweet orange juice (RAI et al, 2004) and sapodilla juice (SIN et al, 2006).…”
Section: Introductionmentioning
confidence: 99%